Synthesis of molecular imprinting polymers for extraction of gallic acid from urine - Bhawani, Showkat Ahmad; Tham, Soon Sen; Mohammad Nasir, bin Mohammad Ibrahim (Springer, 2018)
The molecularly imprinted polymers for gallic acid were synthesized by precipitation polymerization. During the process of synthesis a non-covalent approach was used for the interaction of template and monomer. In the polymerization process, gallic acid was used as a template, acrylic acid as a functional monomer, ethylene glycol dimethacrylate as a cross-linker and 2,2'-azobisisobutyronitrile as an initiator and acetonitrile as a solvent. The synthesized imprinted and non-imprinted polymer particles were characterized by using Fourier-transform infrared spectroscopy and scanning electron microscopy. The rebinding efficiency of synthesized polymer particles was evaluated by batch binding assay. The highly selective imprinted polymer for gallic acid was MIPI1 with a composition (molar ratio) of 1:4:20, template: monomer: cross-linker, respectively. The MIPI1 showed highest binding efficiency (79.50%) as compared to other imprinted and non-imprinted polymers. The highly selective imprinted polymers have successfully extracted about 80% of gallic acid from spiked urine sample. © The Author(s) 2018.